Penyuluhan Masyarakat Melalui Pemanfaatan Tandan Kosong Kelapa Sawit Di Desa Jati Mulyo Kecamatan Dendang Kabupaten Tanjung Jabung Timur Sebagai Media Pembiakan Jamur Tiram (Baglog) - Wiranti, Ayu; Aprilia Putri, Viga; Minarni, Minarni (Pendidikan Sejarah FKIP Universitas JAMBI, 2024)
The service of the Jambi University Pro-Idea Team is located in Jati Mulyo village which is located in Dendang District, East Tanjung Jabung Regency, Jambi Province. The majority of the people of Jati Mulyo Village make their living as oil palm farmers. Waste from empty palm oil bunches is often found in the village. By looking at the existing potential, innovation emerged to utilize TKKS as a medium for cultivating oyster mushrooms, with the hope that waste problems in the industry and oil palm plantations could be reduced. The aim of the Pro- Ide Team's service activities to the community is the use of TKKS waste, empowering the community regarding how to make baglog from TKKS waste as a medium for cultivating oyster mushrooms. The method used in this research is education about the benefits of EFB waste and making baglog as a breeding medium for oyster mushrooms. This activity produces oyster mushroom baglog which can increase the selling value produced, as well as increase the creativity of human resources in Jati Mulyo Village, Dendang District, East Tanjung Jabung Timur, Jambi